DAMPAK KEBIJAKAN INDONESIA MEMBATASI KUOTA IMPOR DAGING SAPI DARI AUSTRALIA - Pulungan, Reni Efrida; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Cooperation begins with the first European settlement residents in Australian who rely on food supplies. Food supplies which are often brought from java. The first ship to arrive in Sydney from Indonesian is Waaksamheyd ship in 1790. Ship was carrying food supplies from Batavia ( Jakarta name at the time ). Food supplies that include: 171 tons of beef, 172 tons of pork, 39 tons of flour, 4,500 pounds of sugar, 31,000 kg of rice. Trade and commerce between Australian and Indonesian are growing. Two-way trade has increased to 25.2% during 2000-2002. More than 400 Australian companies are doing trade in Indonesian, ranging from mining to telecommunications. These companies work as a trading partner with the company and the Indonesian government.This research method is descriptive research, a descriptive study is provide an overview of the problems, circumstances, symptoms, and the actions or policies. In case after Indonesian restrict beef imports from Australian. In 2013 estimated the total national needs as much as 521,000 tons of meat, 441,000 tons of meat from within the country, while 80,000 tonnes Imported. Beef import quota of 80,000 tonnes comprised of 32,000 tonnes of frozen beef cows and 276 thousand equivalent to 48 thousand tons of meat. Public policy is not easy, depending on the political will of the government ( political will ) are realized on economic policy adopted. The only yardstick is how a puublic policy, trade policy can welfare of society in general. In general, the reduction of quota beef imports by the Indonesian government does not affect the political relations of both countries, but the political climate in the country is volatile due to the scarcity of meat in the market, as well as the Australian government is under pressure from the farmers.Keyword : Policy Impact Indonesian, Beef Import Quota Limit of Australian